Performance and evaluation of modified rotary banana slicer - ATHIRA A.S CINU VARGHESE HARITHA MOHANAN; Dr. sudheer K.P (Guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
Performance and evaluation of modified rotary banana slicer
Performance and evaluation of modified rotary banana slicer